2019
DOI: 10.1007/s10589-019-00100-1
|View full text |Cite|
|
Sign up to set email alerts
|

Convergence rate for a Radau hp collocation method applied to constrained optimal control

Abstract: For control problems with control constraints, a local convergence rate is established for an hp-method based on collocation at the Radau quadrature points in each mesh interval of the discretization. If the continuous problem has a sufficiently smooth solution and the Hamiltonian satisfies a strong convexity condition, then the discrete problem possesses a local minimizer in a neighborhood of the continuous solution, and as either the number of collocation points or the number of mesh intervals increase, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…It has been shown in Refs. [23,24,25,26,27] that under conditions of smoothness and coercivity, a Gaussian quadrature direct LGR collocation will converge to a local minimizer of the continuous optimal control problem. A locally minimizing solution may not, however, be obtained when the problem does not satisfy such coercivity conditions (for example, a problem with a nonsmooth optimal control).…”
Section: Lavrentiev Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in Refs. [23,24,25,26,27] that under conditions of smoothness and coercivity, a Gaussian quadrature direct LGR collocation will converge to a local minimizer of the continuous optimal control problem. A locally minimizing solution may not, however, be obtained when the problem does not satisfy such coercivity conditions (for example, a problem with a nonsmooth optimal control).…”
Section: Lavrentiev Gapmentioning
confidence: 99%
“…In addition, a convergence theory has recently been developed using Gaussian quadrature collocation. Research on this theory had demonstrated that, under certain assumptions of the smoothness and coercivity, an hp Gaussian quadrature method that employs either LG or LGR collocation points converges to a local minimizer of the optimal control problem [23,24,25,26,27] While Gaussian quadrature orthogonal collocation methods are well suited to solving optimal control problems whose solutions are smooth, it is often the case that the solution of an optimal control problem has a nonsmooth optimal control [28]. The difficulty in solving problems with nonsmooth control lies in determining when the nonsmoothness occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a p method, the number of intervals is fixed, and convergence is achieved by increasing the degree of the approximation in each interval. To achieve maximum effectiveness, p methods have been developed using orthogonal collocation at Gaussian quadrature points [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. For problems whose solutions are smooth and well-behaved, a Gaussian quadrature orthogonal collocation method converges at an exponential rate [20,21,22,23,24].…”
mentioning
confidence: 99%
“…To achieve maximum effectiveness, p methods have been developed using orthogonal collocation at Gaussian quadrature points [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. For problems whose solutions are smooth and well-behaved, a Gaussian quadrature orthogonal collocation method converges at an exponential rate [20,21,22,23,24]. Gauss quadrature collocation methods use either Legendre-Gauss (LG) points [8,12,13,20,21,22,23], Legendre-Gauss-Radau (LGR) points [11,12,13,14,20,23,24], or Legendre-Gauss-Lobatto (LGL) points [7].…”
mentioning
confidence: 99%